El maltrato infantil y su incidencia en el aprendizaje de los niños y niñas del primer año de preparatoria, primer grado de la escuela Cotogchoa, de la parroquia de Amaguaña de la ciudad de Quito, periodo 2014. Lineamientos alternativos - Gualle Godoy, María Fernanda (2014)
Research on mentions " CHILD ABUSE AND ITS IMPACT ON LEARNING CHILDREN FIRST SCHOOL YEAR, FIRST GRADE SCHOOL COTOGCHOA" AMAGUAÑA PARISH OF QUITO, 2014 PERIOD" . ALTERNATIVE GUIDELINES, it is structured according to the Regulation of Academic Board of the National University of Loja. The general objective was formulated, was Educate parents that child abuse affects the learning of children of First Year High School. Scientific, Deductive, Descriptive, Analytical and Statistical: For the development of this research work the following methods were used. The techniques used were: Survey aimed at parents and teachers; and a guide for individual observation applied to the children of the First Year of School for Evaluating learning. From the results of the survey of parents, it came to the conclusion that: 24% of children suffer physical abuse, 2% were sexually abused, 11% suffer from neglect, 3% suffer from emotional abuse and 60% of children are not abused. It is concluded that 40 % if the abuse affects learning in children while 60 % No impact for them